Innovative approaches in physical education: leveraging cognitive activation to boost student outcomes - Zha, Haoran; Ding, Xia; Li, Wenye (Frontiers in Psychology, 2025)
IntroductionPhysical education (PE) often struggles with suboptimal student engagement, which impedes the development of physical competence and lifelong health habits. This challenge is especially acute in under-resourced areas like Southwest China. Cognitive Activation Teaching Strategies (CATS), which promote higher-order thinking, offer a potential solution. This study, therefore, aimed to investigate the impact of CATS on primary school students’ physical performance and health behaviors, specifically examining the mediating roles of classroom engagement, self-efficacy, motivation, and emotional regulation.MethodsA mixed-methods sequential explanatory design was employed. First, quantitative data were collected from a stratified sample of 929 primary school students and their parents in Southwest China using validated questionnaires. The hypothesized mediation model was then analyzed using Structural Equation Modeling (SEM). Following this, qualitative data were gathered through semi-structured interviews and non-participant classroom observations with 12 purposively selected “high-CATS” teachers to provide deeper insight into the classroom mechanisms at play.ResultsThe SEM results indicated that CATS significantly and positively predicted students’ physical performance and health behaviors. This relationship was strongly mediated by classroom engagement, PE motivation, and particularly, PE self-efficacy. Conversely, the pathway from CATS to emotional regulation was not statistically significant, and emotional regulation did not significantly predict health behaviors. The qualitative findings corroborated the quantitative data, revealing that teachers’ use of goal-setting, progressive challenges, and feedback created a “productive struggle,” which visibly enhanced students’ intrinsic motivation and collaborative engagement.DiscussionThis study provides robust evidence that cognitive activation is a highly effective pedagogical approach in PE. By fostering self-efficacy and motivation, CATS directly enhance in-class engagement and physical performance. The findings suggest that designing PE tasks to be cognitively challenging is crucial for improving student outcomes. However, the limited impact on emotional regulation and out-of-class health behaviors indicates that CATS alone may be insufficient. Educational programs should therefore integrate CATS to boost classroom success while also developing comprehensive, multi-faceted interventions to cultivate emotional skills and promote the transfer of healthy habits beyond the school setting.